Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Factors influencing the expression of human directed dog aggression. A qualitative study of professional opinion - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2026)

Pathological drivers of coral diseases across the Arabian Peninsula - Thierry M. Work; Greta S. Aeby; David Abrego; Jessica Bouwmeester; Emily Howells; Pedro Range; Maren Ziegler; Thor Jensen; Amanda Shore; Grace Vaughan; John A. Burt; Christian R. Voolstra; et al. (Coral Reefs, 2026)
Increasing trends of coral mortality are a challenge to coral reef management worldwide, and a need exists to identify the causes and pathways involved. Pathology is useful to help decipher potential causes of mortality in animals, because it illuminates agents associated with lesions and gives insights on the nature of how a host responds to said agents. To better understand the nature of threats facing corals in the Arabian Peninsula, we performed gross and microscopic pathology on corals from Saudi Arabia, Qatar, and the United Arab Emirates. Among 321 coral fragments examined from 21 genera, tissue loss was the most common lesion seen in 31% of samples, reflecting its widespread presence on reefs from the Arabian Peninsula. Histologically, 68% of lesions exhibited necrosis, predominantly in the basal body wall and surface body wall. Endolithic filamentous microalgae and sponges, originating from the skeleton, were associated with 57% and 39% of lesions, respectively, and were often linked to necrosis and hyaline membrane formation. Cell-associated microbial aggregates and coccidia were detected mainly in Acropora, Pocillopora , and Porites but were not associated with adverse host response. Notably, 69–100% of fragments showing lesions were female likely reflecting the temporal reproductive life history of corals in the region. Our findings highlight endolithic organisms as major contributors to coral tissue degradation in the Arabian Peninsula. Future studies might focus on drivers of endolithic microalgal and sponge dynamics in the region and their role in coral reef health.

The role of cross-polarization in producing high-resolution pan-Arctic sea ice motion from the RADARSAT Constellation Mission over several years - Alexander S. Komarov; Mathieu Plante; Jean-François Lemieux; Stephen E.L. Howell; Mike Brady (Remote Sensing of Environment, 2026)

Water Exchange Characteristics of Tidally Influenced Hydrilla Invasion Sites in the Lower Connecticut River - Andrew W. Howell; Benjamin P. Sperry; Jens P. Beets; Michael W. Durham; Jonathan S. Glueckert; Amber E. Riner (Estuaries and Coasts, 2026)
The Lower Connecticut River (CR) is an ecologically and recreationally significant ecosystem within New England, but the river has become increasingly vulnerable to the intrusion of aquatic invasive species (AIS) like hydrilla ( Hydrilla verticillata ). The hydrilla population recently discovered in the Lower CR is genetically unlike former hydrilla clades present in the United States. The specific biological and management components of this unique clade-C hydrilla in comparison to its cohorts remains largely undetermined and the nature of management action to combat the submersed plant within the tidally influenced lotic system further complicates waterway resilience efforts due to high-water exchange. Because of the inherent environmental challenges attributed to lotic environs, the use of aquatic herbicides remains the primary management tool for selective and effective hydrilla control. However, knowledge of the site-specific water exchange processes at infested sites coupled with subspecies- and herbicide-specific concentration-exposure time (CET) requirements are essential for successful plant management. The primary goal of the present studies was to quantify bulk water exchange rates at five representative hydrilla infestation sites within the Lower CR using Rhodamine WT dye (RWT) to mimic prospective herbicide application operations. Dye monitoring indicated distinct variability among study site water exchange rates, with RWT half-lives ranging from 0.35 to 72.36 h following application. Future management efforts deploying herbicide should consider these methods and findings when selecting appropriate herbicide active ingredients and use rates to achieve hydrilla control. While the present water exchange findings offer initial guidance, comparable dye studies will be necessary as management programs target additional hydrilla invasion areas within the river.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Rapamycin Treatment Reduces Brain Pericyte Constriction in Ischemic Stroke - Daniel J. Beard; Lachlan S. Brown; Gary P. Morris; Yvonne Couch; Bryan A. Adriaanse; Christina Simoglou Karali; Anna M. Schneider; David W. Howells; Zoran B. Redzic; Brad A. Sutherland; Alastair M. Buchan (Translational Stroke Research, 2025)
The contraction and subsequent death of brain pericytes may play a role in microvascular no-reflow following the reopening of an occluded artery during ischemic stroke. Mammalian target of rapamycin (mTOR) inhibition has been shown to reduce motility/contractility of various cancer cell lines and reduce neuronal cell death in stroke. However, the effects of mTOR inhibition on brain pericyte contraction and death during ischemia have not yet been investigated. Cultured pericytes exposed to simulated ischemia for 12 h in vitro contracted after less than 1 h, which was about 7 h prior to cell death. Rapamycin significantly reduced the rate of pericyte contraction during ischemia; however, it did not have a significant effect on pericyte viability at any time point. Rapamycin appeared to reduce pericyte contraction through a mechanism that is independent of changes in intracellular calcium. Using a mouse model of middle cerebral artery occlusion, we showed that rapamycin significantly increased the diameter of capillaries underneath pericytes and increased the number of open capillaries 30 min following recanalisation. Our findings suggest that rapamycin may be a useful adjuvant therapeutic to reduce pericyte contraction and improve cerebral reperfusion post-stroke.

Risk factors for human-directed aggression by dogs: The human side of the problem. A two-part systematic review and narrative synthesis - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2025)

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Development and application of a genetic baseline to inform bull trout (Salvelinus confluentus) passage and conservation in the Snake River - John S. Hargrove; Thomas A. Delomas; Matthew R. Campbell; Philip J. Howell; Audrey C. Harris; Richard Wilkison (Conservation Genetics, 2025)

Quantifying Virtual Field Trip Efficiency - J. H. Pugsley; J. A. Howell; A. J. Hartley; S. J. Buckley; M. Chmielewska; N. Naumann; N. J. Schofield; R. Brackenridge (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)
The efficiency of virtual field trips (VFTs) compared to their physical counterparts, is often regarded as one of their key benefits. Virtual field trips are typically more time, cost and environmentally efficient and logistically easier to plan and execute. This is largely due to the lack of travel, however, the nature of these efficiencies, which is essential for deciding whether a trip should be virtual, physical or blended, have not previously been quantified. Here we present a quantitative evaluation of several measures of efficiency, using data from a like-for-like comparison between 10 day long virtual and physical field trips to Utah, USA, from the University of Aberdeen, UK. For this case study, our results demonstrate that virtual field trips are more efficient across all the categories of time, cost, environmental impact, and logistics. In addition to saved air travel days at the start and end of the physical trip, a further 33.3% of the time on the physical field trip was spent travelling (walking and driving). This time saving allowed an additional 16 localities to be visited on the virtual field trip. The virtual field trip localities also ran in an order that best suited the geological narrative rather than their geographic location which the physical field trip was restricted by. Flights and driven kilometres for the physical trip produced c. 4 t of carbon dioxide equivalent (CO 2 ) per student. The virtual trip produce <1% of the CO 2 and was comparable to a typical teaching week, making it significantly more environmentally efficient. The cost of the virtual trip was negligible compared to that of the physical trip (saving up to £ 3000 GBP per student). These findings were compared to the fulfilment of learning outcomes, quantified primarily through questionnaires, the student responses suggest that the PFT and VFT perceptions of learning outcomes were generally comparable. Efficiency is not the only measure of a successful field trip, with other parameters such as social cohesion and embodiment within the outdoor environment that must also be considered when planning a field trip. Therefore, the authors do not advocate or support an abandonment of physical field trips. Rather, this study aims to provide a first attempt to quantify efficiency to inform decision making when planning field training.

Corrigendum to “Plutonium and other radionuclides persist across marine-to-terrestrial ecotopes in the Montebello Islands sixty years after nuclear tests” [Sci. Total Environ. Volume 691, 15 November 2019, pages 572–583] - M.P. Johansen; D.P. Child; T. Cresswell; J.J. Harrison; M.A.C. Hotchkis; N.R. Howell; A. Johansen; S. Sdraulig; S. Thiruvoth; E. Young; S.D. Whiting (Science of The Total Environment, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

An Integrative Approach to Weight Management – Patient-centered Medical Home, Wellness Center, and Pharmacology - M. Coy; S. Troxell; B. Roper; K. Russo; O. Erinne; A. Luker; S. Shalak; J. Howell; J. Duhart (Journal of the Academy of Nutrition and Dietetics, 2024)

Relationship Between a High-Fat Diet, Reduced Mobility, and Trace Element Overload in the Olfactory Bulbs of C57BL/6J and DBA/2J Mice - Melissa S. Totten; Jenna M. Howell; Jordan A. Tomberlin; Keith M. Erikson (Biological Trace Element Research, 2024)

Testing a health baseline during a bivalve mollusc mortality event: An investigation into die-offs of pipi Paphies australis from Aotearoa New Zealand - Joanne Howells; Lisa Maria; Taryn Shirkey; Ari Carrington; Henry S. Lane (Journal of Invertebrate Pathology, 2024)

The Fastest Rotators: Near-Earth Asteroids Observed with the Arecibo Planetary Radar System - Luisa Fernanda Zambrano-Marin; Ellen S. Howell; Sean E. Marshall; Jon Giorgini; Flaviane C.F. Venditti (Icarus, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Correction to: The Effects of Long-term, Low-dose β-N-methylamino-L-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

The Effects of Long-term, Low-dose β-N-methylamino-l-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Effects of ketamine treatment on cocaine-induced reinstatement and disruption of functional connectivity in unanesthetized rhesus monkeys - Eric A. Maltbie; Kaundinya S. Gopinath; Leonard L. Howell (Psychopharmacology, 2019)

Deformation-related spectroscopic features in natural Type Ib-IaA diamonds from Zimmi (West African craton) - Karen V. Smit; Ulrika F. S. D’Haenens-Johansson; Daniel Howell; Lorne C. Loudin; Wuyi Wang (Mineralogy and Petrology, 2018)

Episodic diamond growth beneath the Kaapvaal Craton at Jwaneng Mine, Botswana - Michael U. Gress; Daniel Howell; Ingrid L. Chinn; Laura Speich; Simon C. Kohn; Quint van den Heuvel; Ellen Schulten; Anna S. M. Pals; Gareth R. Davies (Mineralogy and Petrology, 2018)

Progress in neuroscience in Africa: editorial - Fleur M. Howells; Jacqueline S. Womersley (Metabolic Brain Disease, 2018)

Species-Specific Coral Calcification Responses to the Extreme Environment of the Southern Persian Gulf - Emily J. Howells; Glenn Dunshea; Dain McParland; Grace O. Vaughan; Scott F. Heron; Morgan S. Pratchett; John A. Burt; Andrew G. Bauman (Frontiers in Marine Science, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Variation in particulate C : N : P stoichiometry across the Lake Erie watershed from tributaries to its outflow - Clay Prater; Paul C. Frost; E. Todd Howell; Susan B. Watson; Arthur Zastepa; Sarah S. E. King; Richard J. Vogt; Marguerite A. Xenopoulos (Limnology and Oceanography, 2017)
Human activities can cause large alterations in biogeochemical cycles of key nutrients such as carbon (C), nitrogen (N), and phosphorus (P). However, relatively little is known about how these changes alter the proportional fluxes of these elements across ecosystem boundaries from rivers to lakes. Here, we examined environmental factors influencing spatial and temporal variation in particulate C : N : P ratios across the Lake Erie watershed from its tributaries to its outflow. Throughout the study, particulate nutrient ratios ranged widely (C : N 2.0–25.8, C : P 32–530, N : P 3.7–122.9), but mean values were generally lower than previous estimates from different aquatic environments. Particulate C : N ratios varied the least across all environments, but C : P and N : P ratios increased between tributaries and coastal areas and throughout the growing season in coastal environments. These ratios also differed temporally in offshore waters as particulate C : P and N : P were higher in the spring and summer and lower in the fall and winter. Particulate C : P ratios also increased between the western/central and eastern basins indicating differential nutrient processing across the lake. These stoichiometric changes were associated with unique environmental factors among ecosystems as tributary stoichiometry was related to terrestrial land use and land cover, coastal ratios were a product of mixing between riverine and offshore waters, and offshore patterns were influenced by differences in temperature and particulate nutrient loading among basins. Overall, by studying changes in particulate C : N : P ratios across the Lake Erie watershed, our study demonstrates the power of using mass balance principles to study nutrient transformations along the aquatic continuum.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Population genetics of reef coral endosymbionts ( Symbiodinium , Dinophyceae) - D. J. Thornhill; E. J. Howells; D. C. Wham; T. D. Steury; S. R. Santos (Molecular Ecology, 2017)
Symbiodinium is a diverse genus of unicellular dinoflagellate symbionts associating with various marine protists and invertebrates. Although the broadscale diversity and phylogenetics of the Symbiodinium complex is well established, there have been surprisingly few data on fine‐scale population structure and biogeography of these dinoflagellates. Yet population‐level processes contribute strongly to the biology of Symbiodinium , including how anthropogenic‐driven global climate change impacts these symbionts and their host associations. Here, we present a synthesis of population‐level characteristics for Symbiodinium , with an emphasis on how phylogenetic affinities, dynamics within and among host individuals, and a propensity towards clonality shape patterns on and across reefs. Major inferences include the following: (i) Symbiodinium populations within individual hosts are comprised mainly of cells belonging to a single or few genetic clones. (ii) Symbiont populations exhibit a mixed mode of reproduction, wherein at least one sexual recombination event occurs in the genealogy between most genotypes, but clonal propagation predominates overall. (iii) Mutualistic Symbiodinium do not perpetually persist outside their hosts, instead undergoing turnover and replacement via the continuous shedding of viable clonal cells from host individuals. (iv) Symbiont populations living in the same host, but on different reefs, are often genetically subdivided, suggesting low connectivity, adaptation to local conditions, or prolific asexual reproduction and low effective population sizes leading to disproportionate success within and among hosts. Overall, this synthesis forms a basis for future investigations of coral symbiosis ecology and evolution as well as delimitation of species boundaries in Symbiodinium and other eukaryotic microorganisms.

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Ecological Role of Submarine Canyons and Need for Canyon Conservation: A Review - Ulla Fernandez-Arcaya; Eva Ramirez-Llodra; Jacopo Aguzzi; A. Louise Allcock; Jaime S. Davies; Awantha Dissanayake; Peter Harris; Kerry Howell; Veerle A. I. Huvenne; Miles Macmillan-Lawler; Jacobo Martín; Lenaick Menot; et al. (Frontiers in Marine Science, 2017)

Reduction of Enteric Viruses by Blueberry Juice and Blueberry Proanthocyanidins - Snehal S. Joshi; Amy B. Howell; Doris H. D’Souza (Food and Environmental Virology, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

PCDD/F and PCB water column partitioning examination using natural organic matter and black carbon partition coefficient models - Nathan L. Howell; Hanadi S. Rifai (Environmental Science and Pollution Research, 2016)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

MITOsym®: A Mechanistic, Mathematical Model of Hepatocellular Respiration and Bioenergetics - Y. Yang; S. Nadanaciva; Y. Will; J. L. Woodhead; B. A. Howell; P. B. Watkins; S. Q. Siler (Pharmaceutical Research, 2015)

Functional connectivity in frontal-striatal brain networks and cocaine self-administration in female rhesus monkeys - K. S. Murnane; K. S. Gopinath; E. Maltbie; J. B. Daunais; Q. K. Telesford; L. L. Howell (Psychopharmacology, 2015)

The Jeffries–Matusita distance for the case of complex Wishart distribution as a separability criterion for fully polarimetric SAR data - M. Dabboor; S. Howell; M. Shokr; J. Yackel (International Journal of Remote Sensing, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Dual-function theranostic nanoparticles for drug delivery and medical imaging contrast: perspectives and challenges for use in lung diseases - M. Howell; C. Wang; A. Mahmoud; G. Hellermann; S. S. Mohapatra; S. Mohapatra (Drug Delivery and Translational Research, 2013)

Effects of methamphetamine self-administration on actigraphy-based sleep parameters in rhesus monkeys - Monica L. Andersen; Maylen P. Diaz; Kevin S. Murnane; Leonard L. Howell (Psychopharmacology, 2013)

Global population divergence of the sea star Hippasteria phrygiana corresponds to the onset of the last glacial period of the Pleistocene - D. W. Foltz; S. D. Fatland; M. Eléaume; K. Markello; K. L. Howell; K. Neill; C. L. Mah (Marine Biology, 2013)

Platelet development in cuboid diamonds: insights from micro-FTIR mapping - D. Howell; C. J. O’Neill; K. J. Grant; W. L. Griffin; S. Y. O’Reilly; N. J. Pearson; R. A. Stern; T. Stachel (Contributions to Mineralogy and Petrology, 2012)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Human In Vitro Models of Ischaemic Stroke: a Test Bed for Translation - Ana Antonic; Emily S. Sena; Geoffrey A. Donnan; David W. Howells (Translational Stroke Research, 2012)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

Detection of periodontal pathogens in newborns and children with mixed dentition - J. R. Cortelli; C. B. Fernandes; F. O. Costa; S. C. Cortelli; M. Kajiya; S. C. Howell; T. Kawai (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A directed miniscreen for genes involved in the Drosophila anti-parasitoid immune response - Laura Howell; Christopher J. Sampson; Miguel J. Xavier; Ekin Bolukbasi; Margarete M. S. Heck; Michael J. Williams (Immunogenetics, 2012)

Neuroimaging and drug taking in primates - Kevin S. Murnane; Leonard L. Howell (Psychopharmacology, 2011)

Acute brain metabolic effects of cocaine in rhesus monkeys with a history of cocaine use - Porche’ Kirkland Henry; Kevin S. Murnane; John R. Votaw; Leonard L. Howell (Brain Imaging and Behavior, 2010)

Breast cancer susceptibility variants alter risk in familial ovarian cancer - A. Latif; H. J. McBurney; S. A. Roberts; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

RASSF1A polymorphism in familial breast cancer - J. Bergqvist; A. Latif; S. A. Roberts; K. D. Hadfield; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Dopamine transporter-related effects of modafinil in rhesus monkeys - Monica L. Andersen; Eileen Kessler; Kevin S. Murnane; Jessica C. McClung; Sergio Tufik; Leonard L. Howell (Psychopharmacology, 2010)

Evaluating eddy covariance cotton ET measurements in an advective environment with large weighing lysimeters - José Luis Chávez; Terry A. Howell; Karen S. Copeland (Irrigation Science, 2009)

Estimating hourly crop ET using a two-source energy balance model and multispectral airborne imagery - José Luis Chávez; P. H. Gowda; T. A. Howell; C. M. U. Neale; K. S. Copeland (Irrigation Science, 2009)

Behavioral and neurochemical effects of cocaine and diphenhydramine combinations in rhesus monkeys - Matthew L. Banks; Monica L. Andersen; Kevin S. Murnane; Rebecca C. Meyer; Leonard L. Howell (Psychopharmacology, 2009)

Radiometric surface temperature calibration effects on satellite based evapotranspiration estimation - J. L. Chávez; P. H. Gowda; T. A. Howell; K. S. Copeland (International Journal of Remote Sensing, 2009)

Remote sensing of contrasting tillage practices in the Texas Panhandle - Prasanna H. Gowda; T. A. Howell; S. R. Evett; J. L. Chavez; L. New (International Journal of Remote Sensing, 2008)

Interoperability of Neuroscience Modeling Software: Current Status and Future Directions - Robert C. Cannon; Marc-Oliver Gewaltig; Padraig Gleeson; Upinder S. Bhalla; Hugo Cornelis; Michael L. Hines; Fredrick W. Howell; Eilif Muller; Joel R. Stiles; Stefan Wils; Erik De Schutter (Neuroinformatics, 2007)

Using the composite variables of reproductive morphology, histology and steroid hormones to determine age and size at sexual maturity for the thorny skate Amblyraja radiata in the western Gulf of Maine - J. A. Sulikowski; J. Kneebone; S. Elzey; J. Jurek; W. H. Howell; P. C. W. Tsang (Journal of Fish Biology, 2006)
Age at size was linked to sexual maturity in 77 male and 93 female thorny skates Amblyraja radiata from the western Gulf of Maine using three criteria: 1) gross reproductive morphology, 2) histology and 3) steroid hormone concentrations. Age‐bias plots and the coefficient of variation from vertebral band counts suggested that the ageing method represented a non‐biased and precise approach to the age assessment of A. radiata . Maturity ogives for males, based on data gathered for clasper length, circulating testosterone concentrations and proportion of mature spermatocysts within the testes, predicted that 50% maturity occurred at a total length ( L T ) of 865 mm and c. 10·90 years of age. For females, maturity ogives, based on data gathered for ovary mass, shell gland mass, follicle size and circulating oestradiol concentrations, predicted that 50% maturity occurred at 875 mm L T and c. 11·00 years of age. Collectively, the results suggest that analysis of several contemporaneous reproductive variables offers an accurate determination of sexual maturity in the thorny skate.

Development of the dopamine transporter selective RTI-336 as a pharmacotherapy for cocaine abuse - F. Ivy Carroll; James L. Howard; Leonard L. Howell; Barbara S. Fox; Michael J. Kuhar (The AAPS Journal, 2006)

Reproductive isolation among morphotypes of the Atlantic seastar species Zoroaster fulgens (Asteroidea: Echinodermata) - Kerry L. Howell; Alex D. Rogers; Paul A. Tyler; David S. M. Billett (Marine Biology, 2004)

Effects of drought on contrasting insect and plant species in the UK in the mid‐1990s - M. D. Morecroft; C. E. Bealey; O. Howells; S. Rennie; I. P. Woiwod (Global Ecology and Biogeography, 2002)
Aim We examined the effects of drought in the summer of 1995 and the subsequent year on contrasting species of plants, moths, butterflies and ground beetles. We tested whether population increases were associated with: (a) species of warm environments (b) species of dry environments (c) species with rapid reproduction (d) species with high rates of dispersal. Location The study was conducted at Environmental Change Network (ECN) sites throughout Great Britain and Northern Ireland. Methods Climate monitoring, recording of plant species in permanent plots, transect walking for butterflies, light trapping for moths and pitfall trapping for carabid beetles were used. Results There was an overall increase in the number of species recorded in permanent vegetation plots between 1994 and 1996, principally among the annual and biennial vascular plants, probably as a result of gap colonization in grasslands. Most butterfly and moth species increased between 1994 and 1995. Among the butterflies, a southern distribution and high mobility were associated with species tending to increase throughout the period 1994–96, whereas declining species tended to have a northern distribution. A similar number of carabid beetle species increased as decreased in the period 1994–96; decreasing species tended to be associated with lower temperatures and wetter soils. Conclusions Current climate change scenarios indicate that the incidence of droughts in the United Kingdom will increase. A series of dry, hot summers could lead to a rapid change in the population of some species although others, including many plants, may be more resilient. This may lead to complex changes in ecosystems and needs to be considered in planning conservation strategies.

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)

Evaluation of crop water stress index for LEPA irrigated corn - Attila Yazar; T. A. Howell; D. A. Dusek; K. S. Copeland (Irrigation Science, 1999)

Telemetry system for monitoring anterior cruciate ligament graft forcesin vivo - E. L. McKee; D. P. Lindsey; M. L. Hull; S. M. Howell (Medical & Biological Engineering & Computing, 1998)